IMPLICATIONS OF PERIODONTAL STATUS IN THE SUCCESS OF DIFFERENT TYPES OF FIXED PROSTHETIC CONSTRUCTIONS - Irina Grădinaru; Loredana Liliana Hurjui; Radu Mircea Sireteanu Cucui; Oana Elena Ciurcanu; Violina Budu; Adina Oana Armencia; Daniela Onișoru; Cristina Iordache; Magda-Ecaterina Antohe (Romanian Society of Oral Rehabilitation, 2022)
Restorative dentistry, in particular whole crown preparation is known to cause gingival recession. Inadequate partial dentures and soft tissue support can cause severe gum recession. Incorrect use of elevators in oral surgery procedures can destroy the alveolar bone of adjacent teeth causing recession. The aim of this study is to evaluate the cumulative factors influencing the final therapeutic success following the lowering of periodontal status with the type of prosthetic restoration performed.We evaluated a total of 80 prosthetic restorations, 20 veneers and 25 zirconia-supported ceramic crowns and 35 metal-ceramic crowns(CCM). The percentage of sites showing a periodontal space depth greater than 3 mm was lower in the porcelain veneer group. The frequency of periodontal pockets of 4 mm was 1% in the buccal surfaces of the veneers, 4% in the CCM buccal surfaces and 2% in the CCM palatal surfaces. There were no statistically significant differences between the determinations made at the sites assessed at the CCM level and those assessed at the veneers level. 1. Subgingival placement of prosthetic restorations has a negative impact on periodontal health and consequently on their aesthetic outcome. Ceramic veneers, due to their preparation requirements and the advantage they offer due to their all-ceramic structure, have the least impact on periodontal health status.